2022
DOI: 10.3389/fcvm.2022.791143
|View full text |Cite
|
Sign up to set email alerts
|

MAGI1 inhibits interferon signaling to promote influenza A infection

Abstract: We have shown that membrane-associated guanylate kinase with inverted domain structure-1 (MAGI1), a scaffold protein with six PSD95/DiscLarge/ZO-1 (PDZ) domains, is involved in the regulation of endothelial cell (EC) activation and atherogenesis in mice. In addition to causing acute respiratory disease, influenza A virus (IAV) infection plays an important role in atherogenesis and triggers acute coronary syndromes and fatal myocardial infarction. Therefore, the aim of this study is to investigate the function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Indeed, siRNA gene silencing has been shown to induce IFN‐dependent agents' expression (MX‐1, OAS, etc.) [12, 13]. In further experiments, we observed that the negative siRNA (neg siRNA) having no specificity to any mRNA was able to increase RNA receptors (TLR3, RIG‐I) and inflammatory agents (RANTES, ICAM‐1) expression 24 h after the transfection.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, siRNA gene silencing has been shown to induce IFN‐dependent agents' expression (MX‐1, OAS, etc.) [12, 13]. In further experiments, we observed that the negative siRNA (neg siRNA) having no specificity to any mRNA was able to increase RNA receptors (TLR3, RIG‐I) and inflammatory agents (RANTES, ICAM‐1) expression 24 h after the transfection.…”
Section: Discussionmentioning
confidence: 93%